DEKONSTRUKSI NARASI PENAKLUKAN: KONSTRUKSI MODEL MISI INKLUSIF BERBASIS MISSIO DEI DALAM BINGKAI INKLUSIVITAS BUDAYA NUSANTARA - Noh Ruku; Galuh Pandandari (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This article critically examines the transformation of Christian mission paradigms from expansion-oriented approaches toward dialogical and relational models within the plural context of the Indonesian archipelago. The study addresses the gap between global developments in missiology and the lack of contextual mission models rooted in Nusantara’s socio-cultural realities. Using a qualitative theological literature review and conceptual analysis, this research engages key frameworks such as missio Dei, contextual theology, and interfaith dialogue. The findings demonstrate that contemporary mission should be understood as participatory involvement in God’s redemptive work through relational presence, cultural embodiment, and social engagement. Based on this analysis, the study proposes an inclusive mission model grounded in local culture, consisting of three dimensions: incarnational, dialogical, and transformational. This model provides a theological and operational framework for churches in Indonesia to develop culturally sensitive mission practices, foster interreligious relationships, and actively contribute to social transformation within plural societies. The novelty of this study lies in its systematic integration of global missiological discourse with the socio-cultural context of Nusantara.